FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN DEVIDEN PADA PERUSAHAAN YANG TERCATAT DI PT BURSA EFEK INDONESIA - RAISSA, FEBRYANNO (Universitas Katolik Widya Mandala Surabaya, 2012)
This study aims to determine the factors that affect dividend policy on companies listed in Indonesia Stock Exchange. Variables used in this study are free cash flow, profitability, debt to equity ratio, and asset growth. Those factors chosen because of its inconsistent affect toward Dividend Payout Ratio. Purposive sampling method used and result in a sample of 41 companies during the 2007 – 2010. The result showed free cash flow and profitability doesn’t significantly affect the dividend payout ratio. Debt to equity positively affects the dividend payout ratio, and asset growth negatively affects the dividend payout ratio.